Confronting The Challenges of Digitalization Electronic Medical Records: A Systematic Review - Evita Kumala Dewi; Ernawaty Ernawaty; Fitri Kurnia Rahayu (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Electronic Medical Records (EMRs) have the potential to significantly improve healthcare efficiency, quality, and accessibility. However, their implementation faces substantial barriers that hinder widespread adoption. This systematic review aims to identify and analyze key barriers to EMR implementation in healthcare facilities. A systematic literature search was conducted in Scopus, PubMed, CINAHL, and Web of Science for studies published between 2014 and 2024. The study selection process according to PRISMA guidelines. A total of 462 studies were screened, 59 full-text articles were assessed for eligibility, and 14 studies met the inclusion criteria for final analysis. Five major barriers to EMR implementation were identified: (1) usability and system design challenges, (2) training and workforce preparedness, (3) technological and infrastructure constraints, (4) financial and resource limitations, and (5) impact on workflow and patient care. These challenges reflect core strategic management principles, underscoring the need for structured planning, adequate resource allocation, and continuous evaluation. Overcoming barriers to EMR implementation requires improving system usability, enhancing workforce training, investing in infrastructure development, securing sustainable financial resources, and optimizing clinical workflows. A strategic, comprehensive approach is essential to facilitate successful EMR adoption, improve patient care outcomes, and support sustainable healthcare system advancement. Keywords: Barriers, Electronic Medical Records (EMR), Healthcare Facilities, Systematic Review, Implementation Challenges.